In Vivo Confocal Microscopy of Prominent Conjunctival and Corneal Nerves in Multiple Endocrine Neoplasia Type 2B. Issue 11 (November 2019) - Lam, Delphine; Villaret, Jeremie; Nguyen Kim, Pauline; Gabison, Eric; Cochereau, Isabelle; Doan, Serge
Abstract : Objective: To report a case of a patient affected by multiple endocrine neoplasia type 2B (MEN 2B) with imaging of conjunctival neuromas by in vivo confocal microscopy (IVCM). Methods: Case report. Results: A 48-year-old patient affected by MEN2B complained of progressive visual loss in his right eye and severe red, dry and itchy eyes. Best-corrected visual acuity was 20/63 OD and 20/25 OS. Slit lamp exam showed thickened and turned out lid margins, significant blepharitis, conjunctival injection, multiple presumed subconjunctival neuromas at the bulbar conjunctiva and at the limbus, marked prominence of corneal nerves, exposure keratopathy due to incomplete blinking and corneal hypoesthesia, subepithelial corneal neovascularization and scarring in the mid inferior part of both corneas and bilateral iris nodules. We performed IVCM on conjunctival neuromas, revealing large, thick bundles of nerves with disorganization, prominent loops, bifurcations and dilations measuring as much as 1 mm. The IVCM of corneal nerves demonstrated hypertrophic sub basal plexus. Conclusions: To date, this is the first report which documents conjunctival neuromas by confocal microscopy in MEN2B.